Guidance for reporting 2021 surveillance data on Transmissible Spongiform Encephalopathies (TSE). Issue 2 (8th February 2021) - ,; Ortiz Pelaez, Angel; Papanikolaou, Alexandra; Stoicescu, Anca‐Violeta
Abstract : This guidanceis specifically aimed at guiding the reporting of information to EFSA under the framework of Regulation (EC) No 999/2001. The technical aspects for the reporting of surveillance data on Bovine Spongiform Encephalopathy in bovine animals, scrapieand genotyping in small ruminants (sheep and goats) and Chronic Wasting Disease in cervids are covered. The guidanceexplains the individual data elements of the Standard Sample Description version 2 (SSD2) model which are relevant for the data collection on Transmissible Spongiform Encephalopathies. Thisguidance isintended to support the reporting countries in data transmission using eXtensible Markup Language (XML) data file transfer through the Data Collection Framework according to the protocol described in the EFSA Guidance on Data Exchange version 2 (GDE2).© European Food Safety Authority, 2021